2019
DOI: 10.1016/j.heliyon.2019.e01457
|View full text |Cite
|
Sign up to set email alerts
|

A lignin polymer nanocomposite based electrochemical sensor for the sensitive detection of chlorogenic acid in coffee samples

Abstract: In this study, an innovative nanocomposite of multiwalled carbon nanotubes (MWCNTs), copper oxide nanoparticles (CuONPs) and lignin (LGN) polymer were successfully synthesized and used to modify the glassy carbon electrode for the determination of chlorogenic acid (CGA). Cyclic voltammetry (CV) emphasised a quasi-reversible, adsorption controlled and pH dependent electrode procedure. In cyclic voltammetry a pair of well distinct redox peaks of CGA were observed at the LGN-MWCNTs-CuONPs-GCE in 0.1 M phosphate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…High electrocatalytic activity of oxidized lignin films allowed their use in electrode modification for the amperometric detection of ascorbic acid [4], nicotinamide adenine dinucleotide [5], and ozone [11]. Composites of lignin with nanoparticles and carbon nanotubes were used in electrode modification for the amperometric detection of trinitrotoluene [12] and chlorogenic acid [13].…”
Section: Introductionmentioning
confidence: 99%
“…High electrocatalytic activity of oxidized lignin films allowed their use in electrode modification for the amperometric detection of ascorbic acid [4], nicotinamide adenine dinucleotide [5], and ozone [11]. Composites of lignin with nanoparticles and carbon nanotubes were used in electrode modification for the amperometric detection of trinitrotoluene [12] and chlorogenic acid [13].…”
Section: Introductionmentioning
confidence: 99%
“…From the voltammograms ( Figure 10 A) obtained, it is clear that the peak current increases with the increase of the scan rate where both the anodic peak potential and cathodic peak potential shifts toward more positive and negative side, respectively, indicating that the redox action of AL is quasi-reversible. 47 , 48 As shown in Figure 10 B, a linear dependence of the anodic peak current ( I pa ) with the square root of the scan rate ( v 1/2 ) is observed, which recommends that the electrode reaction is a diffusion-controlled process and the linearity equation can be stated as I pa (μA) = −0.4588 + 121.55 v 1/2 (V/s); R 2 = 0.9963. Figure 10 C shows the plot of log I pa versus log v , which shows linearity ( R 2 = 0.9970) with a slope of 0.53, which is in close proximity with theoretical value of 0.5 for the diffusion-controlled process.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reports concerning polyphenol analysis with CNT-base electrodes. [13][14][15][16] In contrast, there has been only one report on curcumin sensing with CNT-based electrodes, 9 likely because of the hydrophobic nature of the CNT electrode and the fact that as-synthesised CNT is an agglomeration of molecules. In a previous study, we reported on an electrode with CNT-carboxymethyl cellulose (CMC) dispersion.…”
Section: Introductionmentioning
confidence: 99%